Validation and Psychometric Properties of the Spanish Version of King’s Parkinson’s Disease Pain Scale - Yeray González-Zamorano; Marcos Moreno-Verdú; Josué Fernández-Carnero; Jaime Herreros-Rodríguez; Juan Pablo Romero (Parkinson's Disease)
Conclusion: The present study provides evidence that the Spanish KPPS effectively measures pain in individuals with PD, with its total score demonstrating good reliability, minimal measurement error, and adequate criterion and convergent validity.